A COHERENT OFDM SWITCHING-SYSTEM FOR FLEXIBLE OPTICAL NETWORK CONFIGURATION - EBBERG, A; Noé, Reinhold; STOLL, L; SCHIMPE, R (JOURNAL OF LIGHTWAVE TECHNOLOGY)

Monolithic System Integration of Optical Devices, Photodetectors and Analog Transimpedance CMOS Amplifiers - Brab, E.; Hilleringmann, Ulrich; Schumacher, K. (ESSCIRC ’93: Nineteenth European Solid-State Circuits Conference)

Hot Carrier Monitoring in NMOS Transistors by Visible Light Emission - Schonstein, I.; Muller, J.; Hilleringmann, Ulrich; Goser, K. (ESSDERC ’93: 23rd European solid State Device Research Conference)

Micromechanic pressure sensors with optical readout and CMOS-preamplifiers on one silicon chip: Processing and first results - Hilleringmann, Ulrich; Adam, S; Goser, K (ESSDtRC’93)

Lie Semigroups and their Applications

Corwin, L. und F.P. Greenleaf. Representations of Nilpotent Lie Groups and their Applications. (Cambridge University Press, 1990) - Hilgert, Joachim (JBer. DMV)

Simplifying Expressions Involving Radicals - Blömer, Johannes

Resemblance and symmetries of geometric patterns - Alt, Helmut; Blömer, Johannes (Data structures and efficient algorithms)

How to denest Ramanujan's nested radicals - Blömer, Johannes (Proceedings., 33rd Annual Symposium on Foundations of Computer Science)

Periodic Sorting on Two-Dimensional Meshes - Kutylowski, Miroslaw; Wanka, Rolf (Parallel Processing Letters 2)
We consider the following periodic sorting procedure on two-dimensional meshes of processors: Initially, each node contains one number. We proceed in rounds each round consisting of sorting the columns of the grid, and, in the second phase, of sorting the rows according to the snake-like ordering. We exactly characterize the number of rounds necessary to sort on an l × m-grid in the worst case, where l is the number of the rows and m the number of the columns. An upper bound of ⌈ log l⌉ + 1was known before. This bound is tight for the case that m is not a power of 2. Surprisingly, it turns out that far fewer rounds are necessary if m is a power of 2 (and m ≪ l) in this case, exactly min { log m + 1, ⌈ log l⌉ + 1} rounds are needed in the worst case.

Design and development of data visualization systems in a workstation environment - Domik, Gitta; Mickus-Miceli, Kristina D. (Journal of Microcomputer Applications)

Designing User-Centered Interfaces for Astrophysical Software - Domik, Gitta (Proceedings on User Interfaces for Astrophysical Software)

Functional Description of Parallel Processes - Koopman, Pieter; Groenewegen, Luuk; Engels, Gregor (Proceedings of the conference SION Computing Science in the Netherlands (CSN '92), The Netherlands)

Improvement of PV-Performance by Partly Structured Surfaces - Krauter, Stefan; Hanitsch, Rolf (Proceedings of the 6th Photovoltaic Science and Engineering Conference, New Delhi (Indien), 10.–14. Februar 1992, Vol 1, S. 1110.)

Hinweise zur Modellbildung und Simulation des Strahlungseinfalls in PV-Module - Krauter, Stefan (Solar Energy Simulation Workshop der DGS, Oldenburg (Deutschland))

Reflexionsverringerung an PV-Modulen durch partiell strukturierte Deckgläser. - Krauter, Stefan; Hanitsch, Rolf (Tagungsband des Achten Internationalen Sonnenforums, Berlin (Deutschland), 30. Juni – 3. Juli 1992, S. 736–741)

Measuring the Heat–Transfer Coefficient of PV-Modules - Krauter, Stefan; Hanitsch, Rolf; Diwisch, R.; Diwisch, N.

Performance of a Partly Structured Surface at a PV-Module - Krauter, Stefan; Hanitsch, Rolf (Proceedings of the 11th European Photovoltaic Solar Energy Conference and Exhibition, Montreux (Schweiz), 12.–16. Oktober 1992, S. 1351–1354)

Visual Specifications of Conceptual Database Schemata (Abstract) - Engels, Gregor

CADDY: A Highly Integrated Environment to Support Conceptual Database Design - Engels, Gregor; Löhr-Richter, Perdita (Proceedings of the Fifth International Workshop on Computer-Aided Software Engineering (CASE 1992), Montreal (Canada))
This experience report describes the development of the CASE environment CADDY Computer-Aided Design of non-traditional Databases 1 which oflers an integrated set of tools for specifying, analyzing, and prototyping a database application on a conceptual level. This environment was designed and implemented during the last four years at Braunschweig Technical University (Germany). The process of developing this environment consisted of a sequence of development steps, where each step corresponded to (at least) one of five main tasks. The intention of this report is to describe these five tasks. At the end, we will critically reflect on the achieved results and solved problems, but also on still open questions of the CADDY environment.